GE_GERICHTE P/23493/2019 vom 17. November 2020 - GE Cour de justice (2020)
ORDONNANCE PÉNALE;OPPOSITION;CITATION À COMPARAÎTRE;NOTIFICATION IRRÉGULIÈRE;DÉFAUT(CONTUMACE);EMPÊCHEMENT NON FAUTIF | CPP.355.al2; CPP.201; CPP.85.al2